International competition, growth and welfare - Paul J. G. Tang; Klaus Wälde (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
Opening up to trade exposes firms to new competitors. If foreign and domestic firms produce close substitutes, their interaction in the product market forces prices below the monopolistic level. This increased competition induces a shift of demand from monopolistic to oligopolistic varieties and thereby reduces incentives to develop new varieties. This reduces innovation activities and thus the growth rate. Competition always reduces welfare for both domestic and foreign consumers. If the scale and the intensity of competition are large, trade will reduce the welfare level even below the autarky level. Temporary, declining tariffs on all imports and permanent tariffs on oligopolistic varieties are instruments to improve welfare.
Keywords: 330